Determinant Factors Affecting The Value Of Telecommunication Sub-Sector Companies Listed On The Indonesia Stock Exchange For The Period 2018-2022 - Novius, Andri (MUI Kota Pekanbaru, 2023)
The purpose of this study is to determine whether earnings per share, profitability, leverage, sales growth and research and development intensity have a significant effect on firm value. This research method is quantitative research by taking samples using a purposive sampling technique based on predetermined characteristics of 7 telecommunications sub-sector companies listed on the IDX for the 2018- 2022 period. The type of data used is secondary data and the method of analysis used is panel data regression using Eviews. The results showed that the calculation of the hypothesis that is earnings per share has no significant effect on firm value with a significant level of 0.1905 > 0.05. Profitability has a significant positive effect on firm value with a significant level of 0.0015 <0.05. Leverage has no significant effect on firm value with a significant level of 0.1873 <0.05. Sales growth has a significant positive effect on firm value with a significant level of 0.0276 <0.05 and the intensity of research and development has no effect on firm value with a significant level of 0.2800 > 0.05. For simultaneous testing, it is obtained F count of 2.202910 with a probability of 0.000159 <0.05 meaning that earnings per share, profitability, leverage, sales growth and research and development intensity influence simultaneously on firm value.